Download presentation
Presentation is loading. Please wait.
Published byRahul Stickland Modified over 10 years ago
1
Trigonometry Review Find sin( /4) = cos( /4) = tan( /4) = Find sin( /4) = cos( /4) = tan( /4) = csc( /4) = sec( /4) = cot( /4) = csc( /4) = sec( /4) = cot( /4) =
2
Evaluate tan( /4) A. Root 2 B. 2 C. Root 2 /2 D. 2 / Root 2 E. 1
3
Trigonometry Review sin(2 /3) = cos(2 /3) = tan(2 /3) = sin(2 /3) = cos(2 /3) = tan(2 /3) = csc(2 /3) = sec(2 /3) = cot(2 /3) = csc(2 /3) = sec(2 /3) = cot(2 /3) =
4
Evaluate sec(2 /3) A. -1 B. -2 C. -3 D. Root(3) E. 2 / Root(3)
5
Trig. Derivatives sin’(x) = cos(x) cos’(x) = - sin(x)
6
Trig. Derivatives sin’(x) = cos(x) sin’(x) =
7
sin’(x) =. sin’(x) =
8
Rule 4 says. A. 0 B. 0.5 C. 1 D. 1.5
9
Rule 5 says. A. 0 B. 0.5 C. 1 D. 1.5
10
sin’(x) =. sin’(x) =
11
Trig. Derivatives sin’(x) = cos(x) cos’(x) = - sin(x)
12
If y = sin(x) + 2x 2, find dy/dx A. - cos(x) + 4x B. cos(x) + 4 C. cos(x) + 4x
13
Trig. Derivatives sin’(x) = cos(x) cos’(x) = - sin(x) sin’(x) = cos(x) cos’(x) = - sin(x) A) sin’(0) = cos(0) = 1 A) sin’(0) = cos(0) = 1 B) sin’( /4) = cos( /4) = 0.707 B) sin’( /4) = cos( /4) = 0.707 C) sin’(- /3) = cos(- /3) = 0.5 C) sin’(- /3) = cos(- /3) = 0.5
14
x= 0, 2 /3, - 3 /4 cos’(x) = - sin(x) cos’(x) = - sin(x) A) cos’(0) = - sin (0) = 0 A) cos’(0) = - sin (0) = 0 B) cos’(-3 /4) = - sin(5 /4) = 0.707 B) cos’(-3 /4) = - sin(5 /4) = 0.707 C) cos’(2 /3) = - sin(2 /3) = - 0.866 C) cos’(2 /3) = - sin(2 /3) = - 0.866
15
Evaluate cos’( /2) A. -1 B. -.707 C. 1 D. 0.707
16
Evaluate sin’( /3) A. - 0.5 B. 0.5 C. 0.707 D. 0.866
17
Trig. Derivatives sin’(x) = cos(x) cos’(x) = - sin(x) sin’(x) = cos(x) cos’(x) = - sin(x) tan’(x) = sec 2 (x) cot’(x) = - csc 2 (x) tan’(x) = sec 2 (x) cot’(x) = - csc 2 (x) sec’(x) = sec(x)tan(x) csc’(x) = -csc(x)cot(x) sec’(x) = sec(x)tan(x) csc’(x) = -csc(x)cot(x)
18
Trig. Derivatives Theorem tan’(x) = sec 2 (x) Theorem tan’(x) = sec 2 (x) Proof : tan’(x) = [sin(x)/cos(x)]’ Proof : tan’(x) = [sin(x)/cos(x)]’
19
Trig. Derivatives Theorem tan’(x) = sec 2 (x) Theorem tan’(x) = sec 2 (x) tan’( /4) = tan’( /4) =
20
Trig. Derivatives Theorem tan’(x) = sec 2 (x) Theorem tan’(x) = sec 2 (x) tan’( /4) = sec 2 ( /4) = 2 while tan( /4) = tan’( /4) = sec 2 ( /4) = 2 while tan( /4) = 1
21
Trig. Derivatives Theorem cot’(x) = - csc 2 (x) Theorem cot’(x) = - csc 2 (x) Proof : cot’(x) = [cos(x)/sin(x)]’ Proof : cot’(x) = [cos(x)/sin(x)]’
22
Trig. Derivatives Theorem sec’(x) = sec(x)tan(x) Theorem sec’(x) = sec(x)tan(x) Proof : sec’(x) = [1/cos(x)]’ Proof : sec’(x) = [1/cos(x)]’
23
Trig. Derivatives Theorem csc’(x) = - csc(x)cot(x) Theorem csc’(x) = - csc(x)cot(x) Proof : csc’(x) = [1/sin(x)]’ Proof : csc’(x) = [1/sin(x)]’
24
Trig. Derivatives sin’(x) = cos(x) cos’(x) = - sin(x) sin’(x) = cos(x) cos’(x) = - sin(x) tan’(x) = sec 2 (x) cot’(x) = - csc 2 (x) tan’(x) = sec 2 (x) cot’(x) = - csc 2 (x) sec’(x) = sec(x)tan(x) csc’(x) = - csc(x)cot(x) sec’(x) = sec(x)tan(x) csc’(x) = - csc(x)cot(x)
25
If y = tan(x) sec(x) find the velocity and y’( /3) sec’(x) = sec(x)tan(x) tan’(x) = sec 2 (x) sec’(x) = sec(x)tan(x) tan’(x) = sec 2 (x) y ’ = tan(x)sec(x)tan(x) + sec(x)sec 2 (x) y ’ = tan(x)sec(x)tan(x) + sec(x)sec 2 (x) y’=sec(x)[sec 2 (x)-1] + sec 3 (x)=2sec 3 (x)-sec(x) y’=sec(x)[sec 2 (x)-1] + sec 3 (x)=2sec 3 (x)-sec(x) y’( /3) = 2sec 3 ( /3)-sec( /3) = y’( /3) = 2sec 3 ( /3)-sec( /3) = sin 2 x+cos 2 x=1 dividing by cos 2( x) sin 2 x+cos 2 x=1 dividing by cos 2( x) tan 2 (x)+1=sec 2 (x) tan 2 (x)+1=sec 2 (x)
26
If y = tan(x) cos(x) find the acceleration and y’’( /3) y’ = cos(x) y’ = cos(x) y’’ = -sin(x) y’’( /3)= y’’ = -sin(x) y’’( /3)=
27
If y = tan(x) + cos(x) find the initial acceleration, y’’(0) tan’(x) = sec 2 (x) sec’(x) = sec(x)tan(x) tan’(x) = sec 2 (x) sec’(x) = sec(x)tan(x) y’ = sec(x)sec(x) - sin(x) y’’ = sec(x) sec(x)tan(x) + sec(x) sec(x)tan(x) - cos(x) = 2 sec 2 (x) tan(x) – cos(x) y’’(0) = 2 * 1 * 0 -......
28
y” = 2 sec 2 (x) tan(x) – cos(x) y”(0) =
29
If y = sec(x), find the acceleration, y’’(0) using the product rule on sec’(x).
30
Find the slope of the tangent line to y = x + sin(x) when x = 0
31
Write the equation of the line tangent to y = x + sin(x) when x = 0 A. y = 2x + 1 B. y = 2x + 0.5 C. y = 2x
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.